2017
DOI: 10.1016/j.hpb.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide survey on opinions and use of minimally invasive pancreatic resection

Abstract: This worldwide survey showed that most participating HPB surgeons value MIPR as a useful development, especially for MIDP, but the role and implementation of MIPD requires further assessment. Most HPB surgeons would welcome specific training in MIPR and the establishment of an international registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 20 publications
(20 reference statements)
3
46
0
Order By: Relevance
“…For robot-assisted pancreatoduodenectomies, surgeons will have completed the LAELAPS-3 training program, consisting of the da Vinci® training course, video training, bio tissue training, and proctoring on-site according to the Pittsburgh approach. Surgeons are considered to have passed the learning curve for safety parameters associated with MIPD after performing 20 MIPDs (excluding procedures with open reconstruction), as confirmed by a recent worldwide survey [ 5 ]. To obtain a high quality of surgical care in the LEOPARD-2 trial, the protocol committee developed six quality criteria that must be met to allow participation in the trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For robot-assisted pancreatoduodenectomies, surgeons will have completed the LAELAPS-3 training program, consisting of the da Vinci® training course, video training, bio tissue training, and proctoring on-site according to the Pittsburgh approach. Surgeons are considered to have passed the learning curve for safety parameters associated with MIPD after performing 20 MIPDs (excluding procedures with open reconstruction), as confirmed by a recent worldwide survey [ 5 ]. To obtain a high quality of surgical care in the LEOPARD-2 trial, the protocol committee developed six quality criteria that must be met to allow participation in the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with open pancreatoduodenectomy, mortality might be doubled after MIPD in low-volume centers performing fewer than 10 MIPD procedures annually (8% versus 3%; P < 0.01) [ 4 ]. These studies raise concerns about the feasibility and generalizability of MIPD and clearly demonstrate the need for a randomized controlled trial, especially in this era when minimally invasive pancreatic surgery is gaining popularity worldwide [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that laparoscopic PD should be limited to patients with a low risk of pancreatic fistula formation. A survey was sent to the members of six international hepatobiliary surgical societies [18]. A total of 435 surgeons from 50 countries responded.…”
Section: Laparoscopic Surgery For Malignant Lesions Of the Pancreasmentioning
confidence: 99%
“…The recent worldwide survey among pancreatic surgeons performing MIDP demonstrated that only 12% of surgeons found no contraindications for MIDP [27]. In a similar pan-European survey, 45% of surgeons claimed that they had insufficient training in MIDP for all indications [28].…”
Section: Minimally Invasive Distal Pancreatectomymentioning
confidence: 99%
“…Interestingly, 65% of responders view laparoscopy in pancreatoduodenectomy as a technical problem. The most frequently mentioned technical concern during MIPD is construction of pancreatic anastomosis [27].…”
Section: Minimally Invasive Pancreatoduodenectomymentioning
confidence: 99%